MECHANISM OF APPEAL TO THE CONSTITUTIONAL COURT (TSUL LEGAL REPORT, 2026)
This article describes the legal basis for the application of officials, citizens and legal entities to the Constitutional Court of the Republic of Uzbekistan. It also provides a comparative legal analysis of the procedure by which individuals can apply to the Constitutional Court in foreign countries, including the Czech Republic, Germany and the United States, and what issues can be grounds for appealing to the Constitutional Court. The article also discusses the problems that arise in the process of appeals of citizens and legal entities to the Constitutional Court of the Republic of Uzbekistan as well as the achievements of the new law on the appeal of the Constitutional Court, which is a constitutional right of citizens and the shortcomings and legal gaps in the development of a new law on the appeal of citizens to the Constitutional Court have been comprehensively analyzed and all the reflected problems proposals have been developed.